2011
DOI: 10.1002/anie.201104141
|View full text |Cite
|
Sign up to set email alerts
|

Ionic‐Surfactant‐Coated Burkholderia cepacia Lipase as a Highly Active and Enantioselective Catalyst for the Dynamic Kinetic Resolution of Secondary Alcohols

Abstract: With a coat for activity: A highly active enzyme was prepared by coating Burkholderia cepacia lipase with an ionic surfactant for use in dynamic kinetic resolution (DKR). Important features of this enzyme include: the fastest DKR of 1‐phenylethanol, the highly enantioselective DKR of a wide range of secondary alcohols (RCH(OH)Ar), and the switching of lipase enantioselectivity in DKR depending on the shape of the aliphatic chain (R).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…[10c] Furthermore, Kim and Park reported on the DKR of a few homoallylic alcohols utilizing an ionicsurfactant-coated Burkholderia cepacia lipase (ISCBCL). [16] The method gave high yields and 95-98 % ee.…”
Section: Introductionmentioning
confidence: 94%
“…[10c] Furthermore, Kim and Park reported on the DKR of a few homoallylic alcohols utilizing an ionicsurfactant-coated Burkholderia cepacia lipase (ISCBCL). [16] The method gave high yields and 95-98 % ee.…”
Section: Introductionmentioning
confidence: 94%
“… 54 In addition, the group of Kim and Park has in a recent study demonstrated that complex 3 can be used together with ionic surfactant-stabilized Burkholderia cepacia lipase for the DKR of allylic secondary alcohols at room temperature in excellent yields and ee’s. 55 …”
Section: Development Of More Practical Protocols For the Dkr Of More mentioning
confidence: 99%
“…1). Later, Kim and co‐workers reported the accomplishment of lipase activation through lyophilization with ionic liquids or ionic surfactants [45–48]. Koo and co‐workers also reported efficient activation of lipase through lyophilizaton of ionic liquid type sol‐gel silica [49]; similar activation methods have been demonstrated by several groups [50–57].…”
Section: Introductionmentioning
confidence: 79%